Evaluación de la captura de carbono como criterio para la conservación del ceibo (Ceiba Trichistandra) del Jardín Bótanico de la UTM. - Pazmiño Basurto, Aleida Liseth (2018)
The objective of the present investigation was to estimate carbon capture as a criterion for the conservation of Ceibo (Ceiba trichistandra) in the Botanical Garden of the UTM, for which four evaluation units or plots were established with dimensions of 50m wide by 100m long in the selected area. Using systematic random sampling, all the individuals present in the area could be quantified, obtaining a total of 209 individuals for the calculation of carbon. In the first plot 48 individuals were quantified, in the second 62 individuals, in the third 44 individuals and in the fourth 55 individuals. With the basic information obtained from each one of them, an allometric model could be applied that takes into account the basal area estimate which gave us 28.27 m2, estimate of volume 196.41m3, estimate of forest biomass 141.42 t / ha, in order to estimate the carbon stored in said species, this being 70.71 t C / ha. Taking into account the conservation criteria, the following strategies were elaborated: prepare a database for the registration of the distribution of the species (Ceiba trichistandra), Prepare a manual for monitoring the vitality of forests where the species are found (Ceiba trichistandra) and Reforestation as ecological restoration with the species (Ceiba trichistandra).